The power of diversity : new ways of learning and teaching through learning styles - Prashnig, Barbara (London, United Kingdom : Continuum International Publishing Group, 2008)
Designed as an easy-to-read workbook, this title should appeal to educators, parents and students, business managers and trainers alike. The author has pioneered the introduction of learning styles and techniques in New Zealand schools and companies.
1. The state of the art -- 2. Diversity is our strength -- 3. Learning styles: a not so quiet revolution -- 4. The LSA: still a revolutionary instrument -- 5. Too many provocations? -- 6. Don't teach me: let me learn -- 7. The new look of learning and teaching -- 8 .Staff training in style: effective preparation for student diversity -- 9. Learning styles are life styles -- 10. Opposites attract -- 11. Parents, children and their style differences -- 12. Make changes in style -- 13. The future has already begun.
Includes bibliographical references.
Keywords: LEARNING, PSYCHOLOGY OF